Design practicum water purification and sea water treatment becomes freshwater to increase student creativity SMP on mix purification material - A Adnin; M Arifin; H Sholihin (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This practice uses a distillation device from household waste. The water used for theclarification process is the sewage water from the ditch in Tomba Village in Baubau and thesea water used is sea water from the sea of Baubau city. This research method is ADDIEdevelopment (Analysis, Design, Development, Implementation, and Evaluation). However, thisresearch method only did until the development step. In necessity analysis, the researcheranalyzed literature study and field study. After the stages of next analysis stage is the designstage, researchers design a practicum design and then consulted with a competent lecturer in thefield of water purification and processing of sea water into fresh water. After the design stagethen carried out the stages of development, the researchers conducted the optimization processas much as 3 times. During the optimization process a feasibility assessment of practical designis undertaken. The assessment was conducted by 5 observers of postgraduate chemistryeducation students. Indicator of practical feasibility assessment that is related to mixedseparation material, equipment resistance, practicality of the tool, accuracy of equipment andstudent safety and tool capability of separation is directed from the distillation result in terms ofsmell and taste. The result of percentage of process of appraisal feasibility evaluation 90,90%,90,90%, 93,18%, 93,18% and 93,18%, respectively. The percentage is included in the categoryof excellent interpre- tation, based on the result of the feasibility assessment, the practical designis ready to be implemented in the learning of mixed separation material